Fasad Museum Semarajaya Klungkung sebagai Tinggalan Arkeologi Kolonial - Krishnayana Putra, Komang Bagus (Humanis; Vol 22 No 1 (2018), 2018)
This research highlight the architectural study for façade of Museum Semarajaya. The aims for this research was to acknowledge the form, architecture style, and cultural elements that influenced this façade. Based on this research, I attempted to explain these issues, like how the form and architectural style, and what are these cultural influences. In order to solve these issues, I used some analysis such as qualitative, stylistical, and morphological analyisis and also used Architectural, acculturation, and diffusion theory to develop the research analysis result interpretation. This façade can be classified into Dutch colonial architectural style as an eclecticism style, which has mixed style between colonial and Balinese traditional style. Based on the field observation, there have cultural influences. Such as Balinese influence, seen by its traditional ornaments at the base of this building, also colonial influence by usage of Dutch colonial architecture elements.